2022
DOI: 10.1038/s41393-022-00822-w
|View full text |Cite
|
Sign up to set email alerts
|

The safety of epidural spinal cord stimulation to restore function after spinal cord injury: post-surgical complications and incidence of cardiovascular events

Abstract: The safety of epidural spinal cord stimulation to restore function after spinal cord injury: post-surgical complications and incidence of cardiovascular events',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…This exciting work outlines one of the first clinical trials for transcutaneous spinal cord stimulation and autonomic function. This work complements the recent findings regarding the safety and efficacy of epidural spinal cord stimulation, along with various preclinical findings [6]. As neuromodulation after SCI shows promise, this non-invasive pilot trial will fill a critical gap in the literature and uncover future directions for the use of such stimulation after SCI.…”
Section: Electrical Neuromodulation To Improve Autonomic Function Aft...supporting
confidence: 60%
“…This exciting work outlines one of the first clinical trials for transcutaneous spinal cord stimulation and autonomic function. This work complements the recent findings regarding the safety and efficacy of epidural spinal cord stimulation, along with various preclinical findings [6]. As neuromodulation after SCI shows promise, this non-invasive pilot trial will fill a critical gap in the literature and uncover future directions for the use of such stimulation after SCI.…”
Section: Electrical Neuromodulation To Improve Autonomic Function Aft...supporting
confidence: 60%
“…SCI participants from the ESTAND study that had completed at least 7 of the follow-up sessions were included in this analysis. A detailed description of the study can be found in previous publications ( Darrow et al, 2019 ), ( Pino et al, 2020 ), ( Pino et al, 2022 ). In addition, nine healthy participants were also recruited to undergo the BMCA as controls for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of reporting adverse events in this category was guided by recent reviews indicating that scarce reporting of adverse events is a major limitation in the field [31,37,38,40]. Although reporting of surgical complications associated with implanted electrodes has been reported [71,72], adverse events associated with the delivery of SCS have not (e.g., burns, infections, pain, tissue damage). Notably, we excluded team qualifications, period, and duty cycle from the minimal reporting guidelines, as these characteristics did not meet the agreement cut-off.…”
Section: Figurementioning
confidence: 99%